2012
DOI: 10.4314/gjer.v11i1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Effluent Produced from Ntak Inyang and Iba Oku Slaughterhouses Environment

Abstract: The characteristics of effluent produced in Uyo Capital city slaughterhouses located at Ntak Inyang and Iba Oku were monitored by water and wastewater parameters. The wastewater from the slaughterhouses generally shows a high pollutant strength. The BOD value of 7.25mg/l, DO value of 0.21mg/l, nutrient values of 1.14 and 1.25mg/l, respectively. The heavy metals concentrations recorded are 0.05, 15.5, 16.05, 0.75 and 0.10mg/l for cadmium, zinc, copper, iron and lead with several million colony forming units (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Compatibility of land uses should be basis for location of abattoirs because Osibanjo and Adie (2007) observed that abattoirs are sources of pollution as they are characterized with highly organic solid and liquid wastes and fat. In corroboration of the aforementioned observation, Ukpong (2012) asserts, in spite of the public and international agencies policy focused on this problem, the situation is degenerating and therefore demands greater attention. These degenerating activities at the slaughterhouses have greatly increased the volume of effluents and animals waste released into the environment with negative socioeconomic and health implications.…”
Section: Introductionmentioning
confidence: 72%
“…Compatibility of land uses should be basis for location of abattoirs because Osibanjo and Adie (2007) observed that abattoirs are sources of pollution as they are characterized with highly organic solid and liquid wastes and fat. In corroboration of the aforementioned observation, Ukpong (2012) asserts, in spite of the public and international agencies policy focused on this problem, the situation is degenerating and therefore demands greater attention. These degenerating activities at the slaughterhouses have greatly increased the volume of effluents and animals waste released into the environment with negative socioeconomic and health implications.…”
Section: Introductionmentioning
confidence: 72%
“…A study by Ukpong et al (2013) showed that the poor waste disposal management practiced by slaughterhouses in Uyo, Southern Nigeria, affected groundwater resources in the area by increasing the concentration of toxic chemicals, suspended soli ds, and coliform bacteria in the water, hence posing a threat to inhabitants in the area. AJHSE 5(1) Akpan et al, 2024 | 44 In addition to breeding infectious pathogens and corrupting water quality, the unsanitary management of slaughterhouses across Nigeria has been reported to degrade air and surface water quality (Olayinka et al, 2013), increase human exposure to the pathogen and waterborne diseases such as cholera, typhoid fever, dysentery, diarrhea, and giardiasis (Aworh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%